Fikih Melayu Nusantara era pra kolonial - Mahdalena, Mahdalena (Sekolah Tinggi Agama Islam Negeri Salatiga, 2012)
Fiqh is often perceived as Islam itself. This is becouse the growth of fiqh involves the integration of followers from different backgrounds, languages, cultures and places where human live. Syeikh Abdurrauf Syah Kuala mentioned that language he used in his books was Jawi Pasai language. Aceh pronunciation and writing were conducted in two language, they were Acehnese language and Malay language, because besides Arabic, both languages are official languages in the kingdom of Aceh Darussalam. So, as the product of thought, fiqh does not admit boundaries of space and time. Thatâs why, the fiqh would be undergoing a process âto becomeâ change according to needs.